The implementation of medical assistance fund system in Ministry of Health Malaysia - Yasin, Megat Al Imran; Lidi, Mathew James (Global Academy Publishing House, 2023)
The rapid technological development and the growing use of information communication technology (ICT) in business organizations have become the centre of attention in past few years. This ICT has facilitated the decision-making process of an organization. The use of the latest applications will speed up the process of implementation and monitoring of organizational activities and programs. In this regard, the Medical Assistance Fund (TBP) has been established by the Government to help patients especially B40 groups who cannot afford to seek treatment in Government Hospitals, clinics and Public University Medical Centers. Through the use of the Medical Assistance Fund System (STBP) (Phase 1) on May 2021 in all hospitals throughout Malaysia will speed up the application process and approval to eligible patients. This paper to discuss the policy decision-making process of redeveloping STBP and subsequently the implementation of STBP.